2016
DOI: 10.1227/neu.0000000000001165
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Seizure Freedom With Vagus Nerve Stimulation for Intractable Epilepsy

Abstract: BACKGROUND Neuromodulation–based treatments have become increasingly important in epilepsy treatment. Most patients with epilepsy treated with neuro–modulation do not achieve complete seizure freedom, and, therefore, previous studies of vagus nerve stimulation (VNS) therapy have focused instead on reduction of seizure frequency as a measure of treatment response. OBJECTIVE To elucidate rates and predictors of seizure freedom with VNS. METHODS We examined 5554 patients from the VNS therapy Patient Outcome R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
223
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 228 publications
(247 citation statements)
references
References 112 publications
10
223
2
12
Order By: Relevance
“…Furthermore, while greater QOL improvement was observed in patients of female gender or Caucasian ethnicity in this study, these are not typical predictors of seizure response in VNS studies. However, a predominantly generalized seizure type predicted favorable QOL outcome in the present study, and has also been shown to predict a better seizure outcome in prior VNS studies [16, 19]. This is an important consideration, as patients with primary generalized epilepsy are unlikely to be candidates for surgical resection or ablation.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, while greater QOL improvement was observed in patients of female gender or Caucasian ethnicity in this study, these are not typical predictors of seizure response in VNS studies. However, a predominantly generalized seizure type predicted favorable QOL outcome in the present study, and has also been shown to predict a better seizure outcome in prior VNS studies [16, 19]. This is an important consideration, as patients with primary generalized epilepsy are unlikely to be candidates for surgical resection or ablation.…”
Section: Discussionsupporting
confidence: 53%
“…Complete freedom from seizures is significantly more likely with resective or ablative epilepsy surgery, reported in 50-80% of surgical cases [31], than with VNS, observed in approximately 8% of patients after > 24 months of therapy [19]. With VNS, approximately 50-60% of epilepsy patients achieve ≥ 50% reduction in seizure frequency after 12-24 months of treatment [16], and similar seizure outcomes have been reported with other neurostimulation therapies for epilepsy [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while complete seizure freedom is relatively rare with VNS, seizure freedom rates and predictors were recently examined across 5,554 patients in the VNS Therapy Patient Outcome Registry, and in a systematic literature review of 78 studies including 2,869 patients [52]. Overall, seizure-freedom rates ranged from 3% after zero to four months of treatment to 8% after more than two years of therapy.…”
Section: Neurostimulation Proceduresmentioning
confidence: 99%
“…Overall, seizure-freedom rates ranged from 3% after zero to four months of treatment to 8% after more than two years of therapy. Predictors of seizure freedom included age of epilepsy onset of greater than 12 years and a predominantly generalized seizure type [52]. Overall, when resective epilepsy surgery is not a viable treatment option, or in individuals who have failed open surgery, VNS may represent worthwhile palliative therapy for pharmacoresistant epilepsy.…”
Section: Neurostimulation Proceduresmentioning
confidence: 99%